Design and fabrication of small scale trainer aircraft - Arunan, Siwaraju (2010)
This is a study on the designing of small scale trainer aircraft by using balsa wood and plywood. The objective of this paper is to design and fabricate small scale trainer aircraft that will avoid crash landing by using an aerial drop modules technology such as parachute, anti-crash servo and night mode kits for night flying. Based on the design, we can measure it weight and it is to be 2.83 kg and wing span of 1.5 m. The existing small scale trainer aircraft available in market is subject to crash landing due to pilot at ground unable to control the aircraft. Besides that, flying the radio controlled at evening is common and preferred by most of the instructor. For more challenging and fun fly, night mode will give more added challenge and experience. Hence, to avoid crash landing, parachute will be used and night mode kits will be installed. In terms of design, I preferred to choose glow engine powered trainer aircraft compared to aircraft powered by motor due to high power. This aircraft is designed based on Federal Aviation Regulations (FAR). Little early assumption with project scope to be followed will help to design complete structure of the trainer aircraft over the two semesters. This report consists of full details on designing the aircraft to get the parameters that involved in the entire project.